Domanic deposits of the Volga-Ural basin – types of section, formation conditions and prospects of oil and gas potential - A.V. Stoupakova; G.A. Kalmykov; N.I. Korobova; N.P. Fadeeva; Yu.A. Gatovskii; A.A. Suslova; R.S. Sautkin; N.V. Pronina; M.A. Bolshakova; A.P. Zavyalova; V.V. Chupakhina; N.N. Petrakova; et al. (Georesursy, 2017)
The Domanic deposits of the Volga-Ural oil and gas basin are a high-carbon thin-bedded formation capable of both producing hydrocarbons with its own oil and gas bearing strata and concentrating them in separate reservoirs and zones (Stoupakova et al., 2015). Formation of the Domanic deposits occurred in a relatively deep basin, during the filling of which a variety of sedimentation environments arose from relatively deep sea to shallow-marine. The peculiarity of the formation conditions of high-carbon strata is the increased content of organic matter, carbonate material and free silica, the source of which could be hydrotherms or volcanogenic products, creating a special gas regime of the Earth’s atmosphere in the late Devonian. Evaluation of the generation potential of the Domanic formation showed that siliceous-carbonate and carbonate-siliceous rocks enriched with marine algal organic matter have a high potential. The greatest prospects of oil bearing are the deflections formed on the site of the avlakogen and their slopes, where deposits, rich in organic matter, were formed practically throughout the late Devonian-Tournaisian. High prospects have slopes of uplifts or sides of reef bodies. Such incisions are distributed on the sides of troughs of uncompensated immersion and the lower parts of uplift slopes adjacent to them. In the domanonicoid deposits, in which the carbonate material predominates, the high-carbon intervals developed along the biohermic structures.